The prevalence of elevated blood pressure in a sample of slovene children and adolescents: a pilot study - Hertiš Tjaša; Petek Tadej; Marčun Varda Nataša (Sciendo, 2018)
The aim of our study was to determine the prevalence of prehypertensive and elevated blood pressure in the hypertensive range (elevated BP) and obtain some anthropometric measures in Slovene children and adolescents.